Glucose‐coated superparamagnetic nanoparticle‐catalysed pyrazole synthesis in water†. (17th October 2016) - Esfandiary, Naghmeh; Nakisa, Athar; Azizi, Kobra; Azarnia, Jamshid; Radfar, Iman; Heydari, Akbar
Abstract : A green, benign, heterogeneous, superparamagnetic catalyst (Glu.@Fe3 O4 ) was synthesized and characterized using Fourier transform infrared spectroscopy, X‐ray diffraction, thermogravimetric analysis, scanning electron microscopy and vibrating sample magnetometry. The prepared catalyst was used to achieve a high‐efficiency, low‐cost, eco‐friendly and easy‐to‐handle protocol for synthesizing substituted pyrazole derivatives from aldehydes, malononitrile and phenylhydrazine. The catalyst was also used in chromene synthesis. Glucose coated on magnetic nanoparticles provided excellent catalytic activity. The catalyst could be recycled for up to four runs without significant loss in catalytic activity. Abstract : Preparation of a High efficient, low‐cost, eco‐friendly heterogeneous superparamagnetic catalyst (Glu.@Fe3 O4 ) for the synthesis of pyrazole.